The identification of thresholds of starch phosphate and amylose levels on multi-scale structures and functional properties of potato starch - Yaqi Hu; Daraz Ahmad; Li Ding; Haroon Rasheed; Andreas Blennow; Jacob Judas Kain Kirkensgaard; Jinsong Bao (Carbohydrate Polymer Technologies and Applications)
Both amylose content (AC) and starch phosphate content (SPC) play important roles in determining the functional features of starch in potato (Solanum tuberosum L.) tubers. However, the relative contribution of these two factors on starch properties has not been determined. The SPC, AC, and various multi-scale structures and functional properties of 13 natural potato starches with varying SPC (ranging from 449 ppm to 1004 ppm) and AC (from 18.8 % to 27.8 %) were investigated. It was found that SPC is closely correlated with the length and proportion of branch chains, and potato starches with high SPC tended to have a lower proportion of amylose. An elevation in SPC significantly enhanced the surface layer ordering of starch granules, while an increase in AC restricted the expansion of starch granules. With a critical SPC of 700 ppm, when the SPC of potato starch surpassed this threshold, phosphate played a predominant part in conferring the functional properties to the potato starch. An increase in SPC boosted the swelling capacity and lessened short-term retrogradation and strength of the starch gel. Conversely, when the SPC fell below this threshold, the influence of AC became more prominent. A higher AC promoted short-term retrogradation and strength of the starch gel. The results of this study further elucidates the subtle interplay between AC and SPC, providing deeper insights into the relationship between phosphate and amylose content and the structure and function of potato starch.